2020
DOI: 10.1007/s40843-020-1453-0
|View full text |Cite
|
Sign up to set email alerts
|

Tunable magnetism in layered CoPS3 by pressure and carrier doping

Abstract: Despite extensive research on recently discovered layered ferromagnetic (FM) materials, their further development is hampered by the limited number of candidate materials with desired properties. As a much bigger family, layered antiferromagnetic (AFM) materials represent excellent platforms to not only deepen our understanding of fundamental physics but also push forward high-performance spintronics applications. Here, by systematic first-principles calculations, we demonstrate pressure and carrier doping con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…The extracted coercive field from samples 1 and 2 in Figure b shows a dramatic increase as pressure increases from a threshold pressure of around 4 GPa to around 7.8 GPa. Above 7.8 GPa, we cannot detect any MCD signal due to a structural transition at ∼7.5 GPa accompanied by a ferromagnetic-paramagnetic phase transition (data are not shown). A pressure-induced insulator–metal transition in CrSiTe 3 and CrGeTe 3 has been reported previously. , Although we did not directly observe such an insulator–metal transition, we notice that the pressure-dependent Raman measurements (Figure S4) also reveal negligible peaks above 7.8 GPa at room temperature, consistent with a metallic state in CrSiTe 3 .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…The extracted coercive field from samples 1 and 2 in Figure b shows a dramatic increase as pressure increases from a threshold pressure of around 4 GPa to around 7.8 GPa. Above 7.8 GPa, we cannot detect any MCD signal due to a structural transition at ∼7.5 GPa accompanied by a ferromagnetic-paramagnetic phase transition (data are not shown). A pressure-induced insulator–metal transition in CrSiTe 3 and CrGeTe 3 has been reported previously. , Although we did not directly observe such an insulator–metal transition, we notice that the pressure-dependent Raman measurements (Figure S4) also reveal negligible peaks above 7.8 GPa at room temperature, consistent with a metallic state in CrSiTe 3 .…”
Section: Resultsmentioning
confidence: 81%
“…As pressure increases further, the area of hysteresis loop increases and the corresponding coercive field also increases from 0.02 T at 4.6 GPa to 0.17 T at 7.8 GPa. Above 7.8 GPa, we cannot detect any MCD signal due to a structural transition at ~ 7.5 GPa accompanied by a ferromagnetic-paramagnetic phase transition 11 (data are not shown). As summarized in Figure 2b, the coercive field dramatically increases as pressure increases, with a threshold pressure around 4 GPa.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Previous work has shown that external pressure acts as an effective approach to tune the structural, 45 electronic, 35 magnetic, 52–54 and topological 46 properties of layered materials, in particular for bP. 35,45,46 Here, the external pressure is simulated by decreasing the thickness of trilayer bP (defined by the vertical distance between the top and bottom P atoms) to investigate the evolution of the electronic structure.…”
Section: Resultsmentioning
confidence: 99%